2023
DOI: 10.2174/1874467215666220308122716
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-2-3p Inhibits Esophageal Carcinoma Cell Proliferation, Migration, and Invasion via Targeting DNMT3B

Abstract: Purpose: To explore regulatory mechanism of miR-129-2-3p underlying esophageal carcinoma (EC) cell progression and generate new ideas for targeted treatment of EC. Methods: Mature miRNA expression data and total RNA sequencing data of EC in TCGA-ESCA dataset were utilized to explore differentially expressed miRNAs (DEmiRNAs). StarBase database was then utilized to predict targets of miRNA. MiR-129-2-3p and DNMT3B expression in EC cell lineswas assayed through qRT-PCR and Western blot. CCK-8, scratch healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Twenty‐four studies analysed miRNAs in blood or tissue samples (bone biopsies) of fracture patients 45,54–76 . Blood or tissue samples were collected during surgery, subsequently RNA was extracted, and validation of miRNAs was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐four studies analysed miRNAs in blood or tissue samples (bone biopsies) of fracture patients 45,54–76 . Blood or tissue samples were collected during surgery, subsequently RNA was extracted, and validation of miRNAs was performed.…”
Section: Resultsmentioning
confidence: 99%
“…45, Blood or tissue samples were collected during surgery, subsequently RNA was extracted, and validation of miRNAs was performed. In detail, n = 18 studies 45,[55][56][57][59][60][61][62][63][65][66][67][68][69][70][71]74,76 analysed blood samples and n = 11 studies 45,54,55,[64][65][66][67]72,73,75,76 analysed samples collected from bone biopsies. Five studies 45,54,55,65,67 analysed both blood and tissue samples.…”
Section: Mirnas In Fracture Healing: Clinical Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma growth is slowed in vitro and in vivo experiments when a DNMT1 inhibitor is given ( 36 ). Currently, there is no specific research on DNMT3B in glioma, but DNMT3B has been reported to accelerate the occurrence and progression of esophageal cancer ( 38 ), lung cancer ( 39 ), breast cancer ( 40 ), and ovarian cancer ( 41 ), implying that DNMT3B is an essential biomarker in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, their findings also indicated that the inhibitory effect could be counteracted by the additional overexpression of DNMT3B. In this manner, miR-129-2-3p acts as a tumor suppressor in EC cells by targeting and inhibiting DNMT3B [ 26 ].…”
Section: Introductionmentioning
confidence: 99%